ANALISIS STABILITAS SISTEM KEUANGAN DI MASA PANDEMI COVID-19 DI INDONESIA - Novalina, Ade; Rusiadi, Rusiadi; Rangkuty, Dewi Mahrani (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
This study aims to analyze financial system stability (Exchange Rate and Inflation) in Indonesia during the Covid-19 pandemic and analyze the differences in financial system stability (Exchange Rate and Inflation) in Indonesia before and after the covid-19 pandemic. This study used a Simultaneous model approach to determine the significant influence of simultaneous Money Supply (JUB), Interest Rate (SB), Export and Foreign Exchange Reserves (CaDev) on Exchange Rates and Inflation in Indonesia.  The results of research for financial system stability (Inflation) showed that SBI positively influenced inflation, JUB and Exchange Rate negatively affect Inflation, where the results of simultaneous estimates showed that SBI, JUB and Exchange Rate, were able to explain financial system stability (Inflation) of 60.30%. The results of the research for financial system stability (Kurs) showed that CAD, Exports and Inflation negatively affect Inflation, where the results of simultaneous estimates show that CAD, Exports and Inflation, are able to explain financial system stability (Exchange Rate) of 13.42%. The results of the T-Test show that there is no significant difference in Financial System Stability (Exchange Rate and Inflation) in Indonesia before and after Covid-19.